2020
DOI: 10.3390/ijms21134679
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Induces DNA Damage and Activation of Nrf2 Mainly in Tubuli of Mouse Kidneys

Abstract: Hypertensive patients have an increased risk of developing chronic kidney disease (CKD). Many of these patients have increased levels of the blood pressure regulating mineralocorticoid aldosterone. As a protection against aldosterone-induced damage, kidney cells can upregulate key regulators of the antioxidant defense, such as nuclear factor-erythroid-2-related factor 2 (Nrf2). In the present study aldosterone-induced kidney damage and Nrf2 activation in kidney cells of mice treated with three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Again, as previously reported, Aldo treatment in mice did not induce Nrf2 target genes as we previously observed in rats [ 11 , 15 ], consistent with reports of downregulated Nrf2 targets from the human situation in CKD and other animal CKD models [ 5 , 16 ]. Unexpectedly, based on our previously conducted rat study with Sulf as the Nrf2 activator [ 11 ], Sulf had no effect at all on Nrf2 target genes, either alone or in combination with Aldo.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Again, as previously reported, Aldo treatment in mice did not induce Nrf2 target genes as we previously observed in rats [ 11 , 15 ], consistent with reports of downregulated Nrf2 targets from the human situation in CKD and other animal CKD models [ 5 , 16 ]. Unexpectedly, based on our previously conducted rat study with Sulf as the Nrf2 activator [ 11 ], Sulf had no effect at all on Nrf2 target genes, either alone or in combination with Aldo.…”
Section: Discussionsupporting
confidence: 92%
“…That the decreased amount of Keap1 basally has no direct effect on Nrf2 expression has also been observed previously by another group, but does not indicate anything about the posttranslational regulation of Nrf2 [ 37 ]. Looking closer at the localization of Nrf2, in these groups of animals, as in the preparatory experiment [ 15 ], a significantly increased Nrf2 amount was shown in all Aldo-treated groups only in the cortex, not in the medulla of the kidney. Too large interindividual differences among the animals prevented an evaluation of the presence of Nrf2 in the nucleus.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The GSVA analysis of POLR2I showed that many gene sets associated with oxidative stress were downregulated in the POLR2I high-expression groups (Figure 10A), suggesting the potential functions of POLR2I in renal oxidative stress damage associated with HN. Consistent with our enrichment analysis results (Figure 6A), there is evidence that oxidative stress is an important driving factor of the pathogenesis and progression of HN (Wilcox, 2005;Balhorn et al, 2020). Oxidative stress can induce DNA damage, which can be fatal to cells if not repaired (You et al, 2020).…”
Section: Discussionsupporting
confidence: 89%